Migration in the time of revolution : China, Indonesia, and the Cold War - Zhou, Taomo, 1984- (Cornell University Press, 2019)
"Argues that migration and the political activism of Chinese living abroad were important forces in the making of the diplomatic relations between China and Indonesia during the Cold War"--